PEMANFAATAN E-COMMERCE SEBAGAI STRATEGI PEMASARAN PADA BRAND JUMMAKIDS - Septihayati, Yulia; Malik Sidik, Zabar; Noor Zhalifunnas, Isa; Juwanda, Hadi (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2024)
Abstract The purpose of this study is to analyze the effectiveness of using e-commerce in marketing strategies in reaching the target market, including promotion, and attracting it in social media. As well as the extent to which brands follow and respond to the latest children's fashion trends and the extent to which they are able to create relevant and attractive designs. analyzing children's fashion trends and keeping up with the latest innovations, brands can maintain or create competitive advantages, position themselves as the first choice in the eyes of consumers and can understand consumer needs so that they have satisfaction with jummakids. By integrating a strong marketing strategy in the digital era, utilizing e-commerce and social media, and maintaining identity and innovation in design, Jummakids has managed to build customer trust, expand the market, and face the competitive dynamics in the children's fashion industry with increasing success. The research provides in-depth insights into the importance of digital-based marketing strategies in shaping the brand image of children's clothing. The practical implications of this research highlight the need for adaptation to digital marketing trends and the importance of creativity and innovation in reaching consumers in the digital era to maintain and increase market share in the children's clothing industry.